Bile duct carcinoma involving the common channel associated with pancreaticobiliary maljunction shows an extension pattern similar to ductal carcinoma of the pancreas. (20th August 2013) - Yoshida, Nao; Esaki, Minoru; Kishi, Yoji; Shimada, Kazuaki; Ojima, Hidenori; Kanai, Yae; Hiraoka, Nobuyoshi
<x xml:space="preserve">Abstract</x> Biliary tract cancer occurs frequently in patients with pancreaticobiliary maljunction (PBM), although no details of its clinicopathological characteristics have been reported. Here we describe a case of bile duct (BD) cancer that developed in association with PBM. This BD cancer involved the common channel, extended to the main pancreatic duct (MPD) via the common channel, and invaded the pancreatic parenchyma, where its growth and spread, and features of its recurrence, were similar to those of ductal carcinoma of the pancreas. We assumed that MPD extension of BD cancer via the common channel was the reason for its deep spread to the pancreas, since BD cancer usually spreads along the BD and rarely reaches the common channel of the ampulla of Vater. During the follow‐up of patients with PBM, attention should be paid to involvement of the common channel by BD cancer and also to cancer developing silently in the pancreas after extrahepatic BD resection.